Faking literature - Ruthven, K. K. (Cambridge University Press, 2001)
Literary forgeries are usually regarded as spurious versions of genuine literature. Faking Literature argues that the production of a literary forgery is an act that reveals the spurious nature of literature itself. Literature has long been under attack because of its alliance with rhetoric (the art of persuasion) rather than with logic and ethics. One way of deflecting such attacks is to demonise literary forgery: literature acquires the illusion of authenticity by being dissociated from what are represented as ersatz approximations of the real thing. Ruthven argues that literary forgery is the creative manifestation of cultural critique. As a powerful indictment of dubious practices in such activities as literary criticism, book-reviewing and the awarding of literary prizes, literary forgery merits serious attention from cultural analysts, and should be a key component of literary studies. This intriguing book will be of interest to all teachers, students and readers of English literature.